Morphologic features of crystalline lens in cataract patients with different lens sclerosis and axial length - Rui Qin; Jing Ding; Yiyun Liu; Qianqian Lan; Tong Sun; Linbo Bian; Dehai Liu; Xiaoyu Wang; Jiawei Chen; Zhengze Sun; Hong Qi (BMC Ophthalmology)
Abstract Introduction To investigate morphological features of crystalline lens in cataract patients and examine the association between lens nucleus sclerosis, axial length (AL), and lens morphology. Methods This retrospective study consecutive included 285 left cataract eyes at Peking University Third Hospital between July 2022 and June 2023. Lens parameters were measured using CASIA2 and IOL Master 700. Patients were sub-grouped by Emery-Little classification and AL. Statistical and regression analyses were performed. Results Severe nuclear sclerosis (Emery-Little grade IV) exhibited smaller back curvature radii (BCR; P = 0.008), lens diameter (P = 0.005), and greater lens decentration (P = 0.012). Long AL eyes (≥ 25.5 mm) showed higher lens decentration (P = 0.026) and lower lens tilt (P < 0.001). BCR strongly correlated with lens diameter (r = 0.904, P < 0.001). Regression identified lens diameter as the primary predictor of BCR (β = 0.758). Compared with the decentration of the lens (R² = 0.045), tilt is easier to predict (R² = 0.125). Conclusion The degree of lens nucleus sclerosis and axial length may affect the morphologic features of the lens. It may be considered that how the lens morphology with excessive nucleus sclerosis or abnormal axial length impact the efficacy and safety of cataract surgery.